Etika Dakwah Dalam Polemik Gus Miftah dan Penjual Es Teh: Analisis Perspektif Moral dan Sosial - Ady Prasetyo; M. Misbahuddin; Dewi Yunita Sari (IAIN Padangsidimpuan, 2025)
Da'wah which means inviting people toward goodness, should ideally be delivered in a manner that is gentle, wise, and full of wisdom. This principle serves as a fundamental foundation in the practice of da'wah, especially in responding to differences of opinion in public spaces that have become increasingly open due to the rapid development of technology and social media. Recently, a controversy has arisen on social media concerning an interaction between Gus Miftah and an iced tea vendor which has sparked diverse public reactions. This phenomenon raises critical questions regarding the ethical boundaries of da'wah in the digital era. This study aims to analyze Gus Miftah’s actions through the lens of islamic da'wah ethics and Max Weber’s theory of social action. Specifically, the paper explores how the meaning of social action relates to the complex and dynamic values of islamic preaching, and how socio-cultural contexts influence the delivery of religious messages. The findings reveal that Gus Miftah’s actions reflect various dimensions of social action: instrumentally rational, value-oriented rational, affective (emotional), and traditional actions—each representing the distinct characteristics of his preaching style. However, from the perspective of islamic da'wah ethics, a communication style that leans toward sarcasm has the potential to deviate from the core principles of da'wah, which emphasize gentleness, propriety, and exemplary conduct. Therefore, preachers are encouraged to be more prudent and reflective in delivering religious messages. This study recommends the need for evaluation and adjustment of the preaching style to remain relevant to the current context without reducing Islamic ethical and moral values.